(untitled) - Barry, Peter J. (Boston, 2012)
Financial Management in Agriculture, Seventh Edition, introduces students to modern concepts and tools of finance, developed and applied to the agricultural sector. Using case studies, practical problems, and a lucid presentation, the text focuses on planning, analyzing, and controlling business performance in agriculture and related financial markets
Keywords: Nông nghiệp,Agriculture; Tài chính,Quản lý,Finance,Management